The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3111/13696998.2015.1078340
|View full text |Cite
|
Sign up to set email alerts
|

Indirect comparison and cost-utility of dabigatran etexilate and rivaroxaban in the treatment and extended anticoagulation of venous thromboembolism in a UK setting

Abstract: The cost-effectiveness evaluations showed that dabigatran can be considered the dominant treatment strategy compared to rivaroxaban in the patients' sub-groups considered, given the projected marginally higher clinical benefits and lower treatment costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…While apixaban, edoxaban, and rivaroxaban have a better safety profile over VKA for the acute management [3942], DOAC were only associated with trends for reduced MB and their net clinical benefit were similar during extended anticoagulation compared to VKA. Pharmacoeconomic studies also suggested that apixaban, dabigatran and rivaroxaban were cost-effective alternatives to VKA for extended anticoagulation following acute VTE in Canada, United Kingdom, and United States of America [4751], although these studies were funded by pharmaceutical companies. Ultimately, the choice of treatment for extended anticoagulation thus likely relies on patients’ preference and individual risk factors for adverse events with VKA and DOAC.…”
Section: Discussionmentioning
confidence: 99%
“…While apixaban, edoxaban, and rivaroxaban have a better safety profile over VKA for the acute management [3942], DOAC were only associated with trends for reduced MB and their net clinical benefit were similar during extended anticoagulation compared to VKA. Pharmacoeconomic studies also suggested that apixaban, dabigatran and rivaroxaban were cost-effective alternatives to VKA for extended anticoagulation following acute VTE in Canada, United Kingdom, and United States of America [4751], although these studies were funded by pharmaceutical companies. Ultimately, the choice of treatment for extended anticoagulation thus likely relies on patients’ preference and individual risk factors for adverse events with VKA and DOAC.…”
Section: Discussionmentioning
confidence: 99%
“…Other events were chronic thromboembolic pulmonary hypertension, post thromboembolic syndrome, and intracranial bleed. These clinical events were evaluated over patient lifetime, 26,27,29,32 except for Amin et al where the events were evaluated on annual basis. 28,30,31…”
Section: Resultsmentioning
confidence: 99%
“…Among the 7 included studies, 3 were conducted in the United States, 28,30,31 2 in the United Kingdom, 26,32 and 2 in Canada. 27,29 The most common measure for the cost-effectiveness evaluation was cost/ICAR (QALY), and it was used in 4 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, broader genotyping packages exist, for example including other genes like CYP2C19 and CYP2C9 . For such packages, even higher test costs of $914 (€1106) are reported [46]. Nevertheless, many patients aged > 60 years will receive polypharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%